Prevalence of Risk Factors of Coronary Heart Diseases among Tribal Population of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Coronary heart diseases (CHDs) are considered as the leading cause of death. List of both modifiable and non-modifiable risk factors for CHDs are long and no particular group of people is immune from it. Tribal populations of Bangladesh are group of people having their own customs and traditions.Objectives: To determine the prevalence of risk factors of CHDs among the tribal population of Chattagram Hill Tracts, Bangladesh.Materials and Methods: This descriptive cross-sectional study was conducted from July to December 2017 among 190 Tribal personnel aged over forty years and living in Chattogram Hill Tracts (CHT) of Bangladesh. Respondents’ socio-demographic characteristics, health history and physical activities were collected in a pre-tested questionnaire. Blood pressure (BP), anthropometric and laboratory parameters were measured and categorized as per the standard procedure.Results: Respondents’ positive history of HTN, IHD and DM among male was 22.1%, 17.2% and 20.7% respectively and among female was 18.6%, 14.5% and 15.9% respectively. BP status was; stage2 HTN, Stage1 HTN and elevated BP among male respondents was 6.9%, 9.7% and 11.7% respectively; in contrary among female respondents it was 4.8%, 6.9% and 9.0% respectively. According to BMI status, 3.4% male and 4.8% female was obese and 15.9% male and 19.3% female was overweight. Regarding biochemical risk factors; by FPG value 9.0% male and 11.7% female respondents were diabetic and 18.6% male and 14.5% female respondents were pre-diabetic. Total cholesterol level was very high, high and borderline high among male respondents was 5.5%, 9.6% and 22.1% respectively and among female respondents 7.6%, 13.1% and 25.5% respectively. TAG level was very high, high and borderline high among male respondents was 6.2%, 9.0% and 17.9% respectively and among female respondents 7.6%, 11.0% and 15.9% respectively. LDL cholesterol level was very high, high and borderline high among male respondents was 6.9%, 11.0% and 18.6% respectively and among female respondents 4.8%, 7.6% and 15.2% respectively. HDL cholesterol level was lower than normal among 10.3% male respondents and 5.5% among female respondents.Conclusion: Prevalence of both modifiable and non-modifiable risk factors of CHDs was less among tribal population. Tribal people’s lifestyle and food habits might have positive impact. Targeted interventions can be implemented to reduce modifiable risk factors and prevent CHDs.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 151-154